2021
DOI: 10.3390/vaccines9121382
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Recombinant NP and M1-Induced Cellular Immune Responses and Protection by Physical Radiofrequency Adjuvant

Abstract: Nucleoprotein (NP) and matrix protein 1 (M1) are highly conserved among influenza A viruses and have been attractive targets to develop vaccines to elicit cross-reactive cytotoxic T lymphocytes (CTLs). Yet, external antigens are often presented on major histocompatibility complex class II molecules and elicit humoral immune responses. In this study, we present a physical radiofrequency adjuvant (RFA) to assist recombinant NP and M1 to elicit potent CTL responses. We found recombinant NP/M1 immunization in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Regarding cross-protective mechanisms, it might be due to the induction of cross-reactive cytotoxic T lymphocyte (CTL) responses in the absence of significant HI titers elicited against heterologous or heterosubtypic viral strains (data not shown). In support, our prior studies found RFA could elicit potent CTL responses against OVA, rHA, and NP/M1 18,20 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Regarding cross-protective mechanisms, it might be due to the induction of cross-reactive cytotoxic T lymphocyte (CTL) responses in the absence of significant HI titers elicited against heterologous or heterosubtypic viral strains (data not shown). In support, our prior studies found RFA could elicit potent CTL responses against OVA, rHA, and NP/M1 18,20 .…”
Section: Discussionsupporting
confidence: 81%
“…RFA boosts seasonal influenza vaccination. Our previous studies found the physical RFA could enhance the efficacy of influenza pandemic 2009 H1N1 vaccine, split virion H5N1 vaccine, and intracellular NP/M1 vaccine [18][19][20] . It remained to be explored whether RFA was also effective to boost seasonal influenza vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further found RFA showed a similar or better adjuvant effect than MF59‐like AddaVax adjuvant to boost pdm09 vaccination depending on vaccine doses 22 . Recently, we found RFA could also significantly enhance recombinant nucleoprotein (NP)‐induced cellular immune responses and confer significant protection against lethal viral challenges in murine models 23 . Physical RFA has the advantage that it does not need to be mixed with vaccines and it can be stored at room temperature and conveniently used to boost vaccination.…”
Section: Introductionmentioning
confidence: 92%
“…22 Recently, we found RFA could also significantly enhance recombinant nucleoprotein (NP)-induced cellular immune responses and confer significant protection against lethal viral challenges in murine models. 23 Physical RFA has the advantage that it does not need to be mixed with vaccines and it can be stored at room temperature and conveniently used to boost vaccination. This study explored whether the physical RFA could significantly enhance H5N1 vaccine immunogenicity and protective efficacy in murine models.…”
Section: Introductionmentioning
confidence: 99%